Coppinsiella extremiorientalis (Teloschistaceae, lichenized Ascomycota), a new species from the Russian Far East and a new genus to the region - FROLOV, IVAN V.; PROKOPIEV, ILYA A.; YAKOVCHENKO, LIDIA S.; GALANINA, IRINA A.; EZHKIN, ALEXANDER K. (Phytotaxa, 2022)
A new epiphytic species of crustose Teloschistaceae, Coppinsiella extremiorientalis, is described from the floodplain forests of the boreal zone of the Russian Far East. It is characterized by its white to whitish grey, thin to disappearing thallus mostly without anthraquinones, dull orange zeorine pruinose apothecia with an anthraquinones composition corresponding to chemosyndrome A. Phylogeny of the genus Coppinsiella, which was previously unknown in the Far East, is discussed, as well as the morphology, ecology and geographical distribution of Coppinsiella species. A new combination for Caloplaca fiumana, an older name for Coppinsiella orbicularis, is also formally proposed.